2010
DOI: 10.1002/ajhb.21073
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and later psychosocial development in the Philippines

Abstract: Objectives-Evaluate whether breastfeeding duration predicts later psychosocial development in a large low socioeconomic status (SES) sample in the Philippines.Methods-The sample consists of 2,752 children aged 5-6 years who were measured in 2004 as part of the Philippine government's Early Childhood Development Project (ECD). Duration of any breastfeeding was the primary independent variable in regression models predicting a cumulative index of psychosocial development that has been shown previously to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
(29 reference statements)
0
12
0
1
Order By: Relevance
“…Daniels & Adair 27 and Duazo et al 28 , Oddy et al 8 , Victora et al 9 and Slykerman et al 41 , all suggested that shorter breastfeeding duration may be associated with higher cognitive ability scores 27 , higher psychosocial development scores 28 , fewer internalization problems 8 , better school performance 9 and better performance in IQ tests 41 . However, the association reported in these articles was not assessed as a breastfeeding duration of less than two years is beyond the scope of this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daniels & Adair 27 and Duazo et al 28 , Oddy et al 8 , Victora et al 9 and Slykerman et al 41 , all suggested that shorter breastfeeding duration may be associated with higher cognitive ability scores 27 , higher psychosocial development scores 28 , fewer internalization problems 8 , better school performance 9 and better performance in IQ tests 41 . However, the association reported in these articles was not assessed as a breastfeeding duration of less than two years is beyond the scope of this review.…”
Section: Discussionmentioning
confidence: 99%
“…Duazo et al 28 analyzed data from a cohort study of 2,752 children aged five to six years in the Philippines. Follow-ups were conducted at yearly intervals, with a total of four surveys completed by the end of the study in 2005.…”
Section: Prevalence Of Breastfeeding Up To Two Years Of Age or Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that duration of breastfeeding is positively related to performance in intelligence tests or achieved schooling, [5], [26][33] whereas other ones have observed a non-linear association, with a decrease in the effect of breastfeeding among those subjects who are breastfed for longer periods [8], [25], [34][37]. This heterogeneity among the studies may be due to differences in the categorization of breastfeeding duration, seven of the nine studies reporting a linear trend had >4 or >6 months as the highest category for breastfeeding duration, whereas the decrease in the effect of breastfeeding was observed among children breastfed for a longer time, ranging from 26+ weeks [34] to 24+ months [25], [35]. We also assessed the effect of the continuous variable duration of breastfeeding in months and the analyses carried out for each site were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…These two studies did not report any impact (positive or detrimental) of breastfeeding for 2 years or more on child development. (Daniels & Adair, ; Duazo, Avila, & Kuzawa, ). A study from the Millenium Cohort Study reported that longer duration of breastfeeding was associated with better educational achievent at age 5 (Heikkila, Kelly, Renfrew, Sacker, & Quigley, ).…”
Section: Introductionmentioning
confidence: 99%